PERHITUNGAN ANGKA LEMPENG TOTAL BAKTERI PADA TELUR AYAM RAS - Surahmaida Surahmaida; Sri Nurhatika (FMIPA : Universitas PGRI Adi Buana, 2018)
Poultry farm chicken eggs is one of the favorite food for society besides meat and fish, because it is highly nutritious, versatile and cheaper than other eggs. The sample of this research uses 8 (eight) samples of poultry farm chicken eggs. This study aims to determine the quality of poultry farm chicken eggs microbiology based on the total plate count of bacteria. The results showed average the total plate count of bacteria on 8 chicken eggs is 104 CFU/ml. This shows that the results still qualified the standard defined by BPOM that is 107 CFU/ml and its mean poultry farm chicken eggs is safe for consumption. Keywords: Poultry farm chicken eggs, Total Plate Count of Bacteria